Line Five of the Amman Citadel Inscription: History of Interpretation and a New Proposal - Burlingame, Andrew (Bulletin of ASOR, 2016)
The fifth line of the Amman Citadel Inscription has remained an interpretive crux since the publication of the text. While earlier studies recognized its importance for the interpretation of the inscription, the philological difficulties hindering interpretation have generated a growing pessimism with respect to this line, culminating in a recent suggestion that it cannot be translated and may simply be the product of scribal mistakes. In this study, I offer a new proposal for the interpretation of this line, accompanied by a review of the previous scholarship devoted to its study. To support this proposal, I call attention to several data that have not been considered in previous studies. Specifically, I argue that {tdlt} at the beginning of the line constitutes a denominative verb meaning "to equip with a door" and point out the overlooked instance of this verb in the Temple Scroll. Second, I offer a new interpretation of {kbh} at the end of the line in light of possible Akkadian and Ugaritic cognates. I aim to illustrate that these proposals allow us to arrive at a more philologically satisfying reading of the line and, in turn, a better understanding of the text as a whole.